2016
DOI: 10.7554/elife.12994
|View full text |Cite
|
Sign up to set email alerts
|

Eighteenth century Yersinia pestis genomes reveal the long-term persistence of an historical plague focus

Abstract: The 14th–18th century pandemic of Yersinia pestis caused devastating disease outbreaks in Europe for almost 400 years. The reasons for plague’s persistence and abrupt disappearance in Europe are poorly understood, but could have been due to either the presence of now-extinct plague foci in Europe itself, or successive disease introductions from other locations. Here we present five Y. pestis genomes from one of the last European outbreaks of plague, from 1722 in Marseille, France. The lineage identified has no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
106
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 36 publications
7
106
0
1
Order By: Relevance
“…Plague invades, fades out, and re-invades alternately existing in animals where some plague natural foci seem to disappear permanently while others re-invades after a rest period of many years. The reasons for plague's persistence, abrupt disappearance in natural environment are poorly understood [2627]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plague invades, fades out, and re-invades alternately existing in animals where some plague natural foci seem to disappear permanently while others re-invades after a rest period of many years. The reasons for plague's persistence, abrupt disappearance in natural environment are poorly understood [2627]. …”
Section: Discussionmentioning
confidence: 99%
“…Through the comparison study of the Qinghai-Tibet plateau plague focus of Marmatahimalayana in Gansu province, we confirmed that the bacterium Y . pestis can long-term persist in the natural plague focus [27, 32] where it exists within the micro-focus in the rest stage, and persists covertly among its hosts and vectors. When the host density increases or abiotic factors change, a local outbreak of plague occurs.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, recent investigations focussing on analysing the genome of historical pathogens with PCR-or NGS-based methods were limited to archaeological skeletal material (e.g., [69][70][71][72][73][74][75][76][77]) or non-archaeological preserved soft tissues (e.g., [78][79][80]). The first successful investigation on non-archaeological, macerated bones assembled in the pathological collection was performed by Baron et al [24]; we have now demonstrated yet again that these bone samples are suitable for extracting analysable amounts of both human and pathogenic DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent decades have been characterized by technology with the ability to rapidly generate serial molecular data from identifiable sources for which we can obtain detailed relevant information through epidemiological surveillance, allowing for the merging of phylodynamics and epidemiology, or evolutionary epidemiology [24,25]. Hence, progress in the field of molecular evolution has provided the opportunity for real-time assessment of the patterns associated with local, national, and global outbreaks [26], cross-species transmission events and characteristics [27], and the effectiveness of treatment strategies on current [28] and recurring epidemics [29]. These assessments are essential for monitoring outbreaks and predicting/preventing pandemic inception, a good example being the recent study of Middle East Respiratory Syndrome coronavirus global transmission [30] (Additional file 1 (Video S1)).…”
Section: Introductionmentioning
confidence: 99%